Biocompatibility of different resin composites after polymerization with two light curing units: an immunohistochemical study - Ipek, Irem; Unal, Murat; Koc, Tulay (Istanbul Univ Press, Istanbul Univ Rectorate, 2023)
Purpose The aim of this study is to compare the biocompatibility of two different resin composites after polymerization under two different light sources in three different time periods. Materials and Methods 72 polyethylene tubes polymerized with 2 different resin composites and 2 different light sources (Elipar S10 and Valo ) [Group 1: Kalore Elipar S10 (KE), Group 2: Kalore Valo (KV), Group 3: Essentia Elipar S10 (EE), Group 4: Essentia Valo (EV)] were implanted in the dorsal connective tissue of 18 rats. 24 empty polyethylene tubes [Group 5: (Control group)] were implanted in the dorsal connective tissue of 6 rats. Then, the rats were sacrificed after 7th, 15th and 30th days in each time intervals (n=8). Biopsy samples were stained with H&E and examined for inflammation, necrosis, macrophage infiltrate, giant cell and fibrous capsule criteria. Immunohistochemical staining was performed to evaluate proinflammatory cytokines (IL-1 beta, IL-6 and IL-8). Results When the composite groups and the control groups were compared; there was difference statistically significant for the criteria of inflammation at 7th and 15th days, there was no statistical difference between the time points in terms of fibrous capsule and necrosis. When the composite groups and control groups were evaluated in terms of proinflammatory cytokines; statistically significant differences were found at 7th, 15th and 30th days. Conclusion All CRs used in this study showed acceptable biocompatibility in the subcutaneous tissues of rats after polymerization with different light sources.
Keywords: Compositeresins; lightsources; biocompatibility; rat; immunohistochemistry